Cultural Intelligence Profile of Junior High School Counsellors and Its Implication on Multicultural Counseling - Ramli, M; Saputra, Nur Mega Aris; Muhayani, Ulfah (Jurnal Kajian Bimbingan dan Konseling, 2024)
The diversity of ethnicities, religions, and races that exist in Indonesia contribute to the country's characterization as a nation with a multitude of cultures. In the context of the relationship between counselor and counselee, cultural diversity is a significant concern. The comprehension, awareness, and work behavior of the counselee's cultural diversity is indicative of the counselor's cultural intelligence. The concept of cultural intelligence is a crucial aspect that counselors must consider when providing multicultural counseling services. The objectives of this research are to determine the description of counselors' cultural intelligence and its application in multicultural counseling. The research employed a quantitative research survey design for junior high school counselors in Malang Regency. For the research instrument, this study employed an intelligence scale adapted from Early and Ang. The data were analyzed descriptively in order to describe the counselor's cultural intelligence profile. The results indicated that metacognitive indicators exhibited the highest proportion, with 40% falling within the very high category, while behavioral indicators exhibited the lowest proportion, with 5% falling within the deficient category. The results of the study indicate that there is a need for counseling assistance in the behavioral aspect of cultural intelligence in order to facilitate the implementation of multicultural counseling. In essence, cultural intelligence represents a form of counselor multicultural competence that is necessary for the implementation of multicultural counseling. An increase in cultural intelligence thus supports an increase in multicultural counseling.